Supporting AI in Logistics Optimization through Data Integration, Real-Time Analytics, and Autonomous Systems - Toluwanimi Adenuga; Noah Ayanbode; Tolulope Ayobami; Francess Chinyere Okolo (International Journal of Scientific Research in Science, Engineering and Technology, 2024)
The integration of artificial intelligence (AI) into logistics systems is reshaping the efficiency and agility of global supply chains. This paper explores the transformative role of AI in optimizing logistics operations through advanced data integration, real-time analytics, and autonomous systems. AI technologies are increasingly applied to enhance core logistics functions such as dynamic routing, intelligent scheduling, and capacity planning, enabling organizations to meet rising customer expectations while minimizing operational costs. The fusion of big data and IoT-enabled supply chains allows for continuous data flow across interconnected logistics networks, providing the foundation for real-time, data-driven decision-making. Key to this evolution is the deployment of digital twins, which create virtual replicas of physical logistics systems to simulate, monitor, and predict performance outcomes under varying conditions. These systems leverage predictive analytics and machine learning algorithms including reinforcement learning to improve resource allocation, identify anomalies, and adapt routing and inventory decisions in real-time. Demand sensing models, informed by structured and unstructured data, further support proactive forecasting and inventory balancing, thereby reducing lead times and avoiding stockouts or overstock situations. Moreover, the integration of predictive maintenance tools within logistics fleets ensures that asset health is continuously monitored, preventing unplanned downtimes and extending vehicle lifespan. Autonomous mobile robots and AI-powered drones are also emerging as vital components in last-mile delivery and warehouse management, offering enhanced speed, accuracy, and scalability. The study presents use cases from multinational logistics providers that have successfully implemented AI-powered platforms, resulting in significant gains in fuel efficiency, delivery accuracy, and supply chain resilience. It also addresses the technical and organizational challenges associated with adopting AI, including data interoperability, cybersecurity, workforce adaptation, and ethical governance. By synthesizing advancements in AI, IoT, and real-time analytics, this paper underscores how intelligent logistics systems are not only enhancing operational performance but also setting new standards for sustainability and customer-centricity in global trade. The findings advocate for continued investment in integrated AI infrastructures to ensure logistics networks are agile, responsive, and future-ready in the face of evolving market demands and global disruptions.
Keywords: Artificial Intelligence; Logistics Optimization; Real-Time Analytics; IoT; Digital Twins; Reinforcement Learning; Predictive Maintenance; Demand Sensing; Autonomous Systems; Supply Chain Resilience